2022
DOI: 10.1021/jacs.2c06860
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Control of Repeating Unit/Sequence/Topology for One-Step Synthesis of Block Polymers from Monomer Mixtures

Abstract: Synchronously and thoroughly adjusting the chemical structure difference between two blocks of the diblock copolymer is very useful for designing materials but difficult to achieve via self-switchable alternating copolymerization. Here, we report self-switchable alternating copolymerization from a mixture of two different cyclic anhydrides, epoxides, and oxetanes, where a simple alkali metal carboxylate catalyst switches between ring-opening alternating copolymerization (ROCOP) of cyclic anhydrides/epoxides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Unlike the time-consuming post-treatment such as Soxhlet extraction, the procedures for material synthesis are evidently simplified. For the synthesis of the conjugated diblock or triblock polymers, a small amount of low M n oligmers or polymer blocks (PM6 and L15 or PY-IT blocks in our case) are indeed included except the majority of ambipolar block copolymers (PM6- b -PY-IT or PM6- b -L15 here) even in quasi-living polymerization and self-switchable alternating copolymerization for conjugated block polymers 53 , 54 . Therefore, the obtained multicomponent polymers S11 (or S9) from the one-pot synthesis method may contain some of PM6, L15 (or PY-IT), and PM6- b -L15 (or PM6- b -PY-IT) due to deactivated polymerization sites, but the block copolymers are in majority 50 , 51 .…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the time-consuming post-treatment such as Soxhlet extraction, the procedures for material synthesis are evidently simplified. For the synthesis of the conjugated diblock or triblock polymers, a small amount of low M n oligmers or polymer blocks (PM6 and L15 or PY-IT blocks in our case) are indeed included except the majority of ambipolar block copolymers (PM6- b -PY-IT or PM6- b -L15 here) even in quasi-living polymerization and self-switchable alternating copolymerization for conjugated block polymers 53 , 54 . Therefore, the obtained multicomponent polymers S11 (or S9) from the one-pot synthesis method may contain some of PM6, L15 (or PY-IT), and PM6- b -L15 (or PM6- b -PY-IT) due to deactivated polymerization sites, but the block copolymers are in majority 50 , 51 .…”
Section: Resultsmentioning
confidence: 99%
“…Satoh and coworkers have shown how multiblock polymers, either block-like or gradient, can be achieved through one-pot mixtures of epoxides/cyclic anhydrides/cyclic esters/cyclic carbonates using simple pivalate salts, with one epoxide and up to six anhydrides. [20][21][22] These studies identified that certain monomer pairs proceeded to polymerization preferentially before others, leading to block copolymer formation. These reports show that there is promise for sequence-controlled block polyesters via ROCOP of epoxides and cyclic anhydrides and that further investigations are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, alkali metal carboxylates have been demonstrated as simple and green initiators for ROAC. [33][34][35][36][37][38] However, a chainend elimination side reaction limits the achievement of endfunctional polymers. Simpler ROAC catalysts for the facile synthesis of end-functional polyesters is highly desirable.…”
Section: Introductionmentioning
confidence: 99%